Composite polymer-bioceramic scaffolds with drug delivery capability for bone tissue engineering. (October 2013) - Mouriño, Viviana; Cattalini, Juan P; Roether, Judith A; Dubey, Prachi; Roy, Ipsita; Boccaccini, Aldo R
<x xml:space="preserve">Abstract</x> Introduction: Next-generation scaffolds for bone tissue engineering (BTE) should exhibit the appropriate combination of mechanical support and morphological guidance for cell proliferation and attachment while at the same time serving as matrices for sustained delivery of therapeutic drugs and/or biomolecular signals, such as growth factors. Drug delivery from BTE scaffolds to induce the formation of functional tissues, which may need to vary temporally and spatially, represents a versatile approach to manipulating the local environment for directing cell function and/or to treat common bone diseases or local infection. In addition, drug delivery from BTE is proposed to either increase the expression of tissue inductive factors or to block the expression of others factors that could inhibit bone tissue formation. Composite scaffolds which combine biopolymers and bioactive ceramics in mechanically competent 3D structures, including also organic–inorganic hybrids, are being widely developed for BTE, where the affinity and interaction between biomaterials and therapeutic drugs or biomolecular signals play a decisive role in controlling the release rate. Areas covered: This review covers current developments and applications of 3D composite scaffolds for BTE which exhibit the added capability of controlled delivery of therapeutic drugs or growth factors. A summary of drugs and biomolecules incorporated in composite scaffolds and approaches developed to combine biopolymers and bioceramics in composites for drug delivery systems for BTE is presented. Special attention is given to identify the main challenges and unmet needs of current designs and technologies for developing such multifunctional 3D composite scaffolds for BTE. Expert opinion: One of the major challenges for developing composite scaffolds for BTE is the incorporation of a drug delivery function of sufficient complexity to be able to induce the release patterns that may be necessary for effective osseointegration, vascularization and bone regeneration. Loading 3D scaffolds with different biomolecular agents should produce a codelivery system with different, predetermined release profiles. It is also envisaged that the number of relevant bioactive agents that can be loaded onto scaffolds will be increased, whilst the composite scaffold design should exploit synergistically the different degradation profiles of the organic and inorganic components.